2020
DOI: 10.3390/antiox9111040
|View full text |Cite
|
Sign up to set email alerts
|

Auranofin Attenuates Non-Alcoholic Fatty Liver Disease by Suppressing Lipid Accumulation and NLRP3 Inflammasome-Mediated Hepatic Inflammation In Vivo and In Vitro

Abstract: Non-alcoholic fatty liver disease (NAFLD) causes liver dysfunction and is associated with obesity and type 2 diabetes. Chronic inflammation is associated not only with the development of NAFLD, but also with hepatic diseases, including steatohepatitis, cirrhosis, and hepatocellular carcinoma. Auranofin is a treatment for rheumatoid arthritis and has recently been reported to have potential effects against a variety of diseases, including inflammation, cancer, and viral infection. In this study, auranofin may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 58 publications
1
23
0
1
Order By: Relevance
“…Previous studies have shown that the activation of NLRP3 is the main cause of STSLS [ 29 ]. It has been proved that auranofin can play an anti-inflammatory role by inhibiting NLRP3 [ 31 , 32 ]. Our results show that for some severely infected patients, auranofin alone or in combination with first-line drugs may be a better choice.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the activation of NLRP3 is the main cause of STSLS [ 29 ]. It has been proved that auranofin can play an anti-inflammatory role by inhibiting NLRP3 [ 31 , 32 ]. Our results show that for some severely infected patients, auranofin alone or in combination with first-line drugs may be a better choice.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Liou et al (2018) reported that fisetin, a naturally abundant flavonoid isolated from various vegetables and fruits, could alleviate hepatic lipid metabolism and improve NAFLD in mice via the activation of the FAO pathway. Recently, Hwangbo et al (2020) showed that auranofin might have potential as a candidate for improving NAFLD symptoms. Auranofin significantly suppressed lipid peroxidation, inflammatory activity, and hepatic steatosis of liver tissues in NAFLD mice induced by a high-fat diet, which attributed to the decreased expression of NADPH oxidase 4 and PPARγ.…”
Section: Implications Of Carnitine Palmitoyltransferase System In Inflammatory Diseases and Cancersmentioning
confidence: 99%
“…In view of the present research, FA metabolism has been attracting considerable interest in hepatic IR injury ( Hwangbo et al, 2020 ), and the role of FAO in the disease is an important research topic (Wang et al, 2020). Luo et al (2021) reported that CPT1A deficiency mitigated inflammation and oxidative stress in carbon tetrachloride-induced liver injury of mice.…”
Section: Implications Of Carnitine Palmitoyltransferase System In Inflammatory Diseases and Cancersmentioning
confidence: 99%
“…The arthritis drug auranofin has also been investigated in the treatment of non-alcoholic fatty liver disease ( Hwangbo et al., 2020 ). Through staining of liver tissue in a mouse model of fatty liver disease, it was shown that auranofin treatment reduced the number of circulating macrophages, which would decrease the amount of inflammatory cytokines secreted.…”
Section: The Il-1 Familymentioning
confidence: 99%
“…This was also shown to be due to the reduction of NLRP3 inflammasome following treatment. Auranofin likely interrupts the formation of the NLRP3 inflammasome in fibrotic liver tissue resulting in the activation of IL-1β by caspase-1 ( Hwangbo et al., 2020 ). The upstream target of auranofin encourages a widespread effect and increased the effectiveness of the drug.…”
Section: The Il-1 Familymentioning
confidence: 99%